Enhancing Vocabulary Skills of Seventh-Grade Students Through Fun Learning - Iqbal Khasani (CV. Mitkom Indotama, 2024)
This research aims to enhance the vocabulary knowledge of seventh-grade students at SMPIT AZ-ZAHRA Sragen through the Fun Learning method. The method was chosen due to a lack of public awareness regarding the importance of learning English. The researchers sought to use this approach to foster enthusiasm for learning English, particularly among female students. Fun Learning is designed to make it easier for students to memorize, spell, and pronounce words in an enjoyable way, ensuring they remain engaged and avoid boredom or drowsiness during lessons. The study was conducted in two cycles, both aimed at improving key areas in the school. The findings indicate that the Fun Learning method was successful, as each student showed progress in mastering vocabulary, and their interest in learning also increased